ChemInform Abstract: Structural and Magnetic Properties of RTiNO2 (R: Ce, Pr, Nd) Perovskite Nitride Oxides. Issue 27 (18th June 2015) - Porter, Spencer H.; Huang, Zhenguo; Cheng, Zhenxiang; Avdeev, Maxim; Chen, Zhixin; Dou, Shixue; Woodward, Patrick M.
Abstract LnTiNO2 (Ln: Ce, Pr, Nd) phases are prepared by solid state ammonolysis of Ln2Ti2O7 precursors by repeated gaseous NH3 treatment during annealing (950 °C, 20 h).